Diffusion of green technology, governance and CO₂ emissions in sub-Saharan Africa - Awa Traoré; Simplice Asongu (African Governance and Development Institute (AGDI), 2023)
Purpose - A promising solution to meet the challenge of sustainability and ensure the protection of the environment consists in acting considerably on the adoption and use of new information and communication technologies. The latter can act on the protection of the environment; completely change manufacturing processes into energy-efficient, eco-friendly techniques or influence institutions and governance. The article attempts to cover shortcomings in the literature by providing a couple of theoretical frameworks and grounded empirical proofs for the dissemination of green technologies and the interaction of the latter with institutional quality. Design/methodology/approach - The sample is made up of 43 African countries covering the period 2000-2020 and a panel VAR modeling approach is employed. Findings - Our results stipulate that an attenuation of CO2 emissions amplifies the diffusion of digital technologies (mobile telephones and internet). Efficiency in the institutional quality of African countries is mandatory for environmental preservation. Moreover, the provision of a favorable institutional framework in favor of renewable energy helps to stimulate environmental performance in African states. Originality/value -This study complements the extant literature by assessing nexuses between green technology and CO2 emissions in environmental sustainability.
Keywords: C52; O31; O33; O43; O55; 330; CO2 emissions; green technology; governance; VAR model